Pengembangan Bahan Ajar Kerangka Tpack Berbasis Video Pembelajaran Pendidkan Agama Islam dalam Meningkatkan Semangat Belajar Siswa - Inayati, Mahfida; Zainab, Nurul (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2023)
In order to foster student enthusiasm in the teaching and learning process, it is very necessary for an educator to process teaching materials well. The purpose of teaching materials is to make it easier for students to understand a lesson delivered by an educator. When there are no teaching materials delivered by the teacher, it is not said to be learning, and when the teaching materials are not used in the teaching and learning process in the classroom, then the teaching materials become a source of learning. The Teaching Material Plan that will be developed is teaching materials with the TPACK framework in PAI BP learning at SMK Al Imron. In this study, the design of the research method uses the Research and Development (R&D) approach, this research and development procedure modifies the Brog & Gall model. Data collection techniques use qualitative descriptive validation which will ultimately describe a result of teaching materials. Data collected through instruments during trials were analyzed using statistics. The development of video-based tpack framework teaching materials is a teaching material that uses ICT. The development of class x pai-bp teaching material products in accordance with ki-kd in chapter 10 with the theme of dignified living in Muslim clothing with several parts including Understanding Muslim Clothing, Muslim Dress Requirements, Muslim Dress Destinations, Muslim Dress Procedures and Muslim Foaming Wisdom. So it can be concluded from various aspects regarding the feasibility of teaching material products for the TPACK framework based on PAI-BP learning videos in class X of SMK Al Imron is very feasible and can increase student teaching enthusiasm as evidenced by the questionnaire that has been given to students with a percentage of 95% that students are very interesting and enthusiastic in learning PAI-BP.